(untitled) (Comillas Journal of International Relations, 2016)
From the early 1930s until his peace time premiership (1951-1955), Winston Churchill was one of the strongest advocates of the concept of a United Europe. While this is well known among scholars of 20th century British history, Churchill’s actual vision for what a United Europe might look like has received less attention. Still less attention has been paid to Churchill’s opinions of the roles other nations might play within the new Europe. This article will examine Churchill’s view of Turkey in the new European order and will reveal that Churchill saw Turkey as a part of, (or at least an extension of) Europe. However, this article will also reveal that Churchill’s conceptualisation of Turkey’s role was largely predicated on 19th century geostrategic thinking.